2007
DOI: 10.1016/j.virol.2007.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A single M protein mutation affects the acid inactivation threshold and growth kinetics of a chimeric flavivirus

Abstract: Numerous viruses of the Flaviviridae family, including dengue, yellow fever, Japanese encephalitis, and West Nile, cause significant disease in humans and animals. The structure and function of the molecular components of the flavivirus envelope are therefore of significant interest. To our knowledge, a membrane (M) protein mutation which affects the pH at which flavivirus particles are inactivated in vitro has never been reported. Here we show that substitution of proline for glutamine at residue M5 (MQ5P) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…In this study, we have isolated and characterized a WNV mutant with increased resistance to the acidotropic agent NH 4 Cl. In contrast to other previously described flaviviruses with altered pH requirements, which exhibited mutations on the proteins that conform the external shell of the virion (E and M) -[34] and references therein-, the WNV mutant here reported displayed a single amino acid substitution on the internal core protein. This amino acid substitution also increased resistance to other acidification inhibitor and induced a reduction of the neurovirulence in mice.…”
Section: Introductioncontrasting
confidence: 91%
“…In this study, we have isolated and characterized a WNV mutant with increased resistance to the acidotropic agent NH 4 Cl. In contrast to other previously described flaviviruses with altered pH requirements, which exhibited mutations on the proteins that conform the external shell of the virion (E and M) -[34] and references therein-, the WNV mutant here reported displayed a single amino acid substitution on the internal core protein. This amino acid substitution also increased resistance to other acidification inhibitor and induced a reduction of the neurovirulence in mice.…”
Section: Introductioncontrasting
confidence: 91%
“…This suggestion is supported by multiple existing studies. The K115E (of prM, or the 26 th amino acid of M) mutation lies adjacent to a region of M that modulates E protein function during early steps of infection such as membrane fusion (Maier, Delagrave et al, 2007). Additional structural studies of the M and E proteins suggest that the first approximately 20 residues of the M protein interact with the ij loop in domain II (dimerization and fusion domain) of E (Zhang, Chipman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…According to this, WNV populations display a variable level of sequence diversity (Ciota et al, 2007;Jerzak et al, 2005) that favours rapid selection of variants in response to selective pressures. Although mutations in the E or M protein that alter pH sensitivity have been described for other flaviviruses (summarized by Maier et al, 2007), this kind of mutant has not been reported for WNV. To gain information on the molecular aspects of the conformational rearrangements of WNV virions following acid exposure, a WNV variant with increased resistance to acidinduced inactivation was isolated and characterized.…”
Section: Introductionmentioning
confidence: 98%